Carbon Content Potential of Mangrove Species in Gili Sulat, East Lombok - Ainun Diniyatushoaliha; Agil Al Idrus; Didik Santoso (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mangroves are a unique ecosystem because they live in two transition zones, always green, and tolerant of salt. However, globally it is under serious threat due to environmental issues that are closely related to deforestation and degradation of mangrove forests. Mangrove ecological services as a carbon sink can help mitigate climate change and global warming. This capability has not been utilized optimally, especially in NTB, specifically Gili Sulat, which has natural mangrove forests. Therefore, this research aims to identify, explain, describe, and understand the carbon content of trees in mangrove species in Gili Sulat. The station determination method is done by purposive sampling. The sampling technique for carbon content was carried out using a non-destructive method, namely measuring the diameter at breast height and tree height. The results of the study found nine mangrove species in the tree category where the highest potential carbon content was found in the species Bruguiera gymnorrhiza, namely 0.285 ton C/ha and 183.255 ton C/643 ha, and the lowest was found in the species Exoecaria agallocha, namely 0.010 ton C/ha and 6.430 ton C/643 Ha. Meanwhile, the total biomass, carbon content, and carbon dioxide absorption of mangrove species in Gili Sulat were 661.004 tonnes/643ha, 331.145 tonnes C/643 ha, and 1212.698 tonnes CO2/643 ha respectively. The high potential carbon content of mangrove tree species in Gili Sulat proves that the ecological services of Gili Sulat's mangroves have a positive impact on climate change mitigation and global warming.